Phyto-Extract-Mediated Synthesis of Silver Nanoparticles (AgNPs) and Their Biological Activities. (16th November 2022) - Adnan, Muhammad; Akbar, Asma; Mussarat, Sakina; Murad, Waheed; Hameed, Ishfaq; Begum, Shaheen; Nazir, Ruqia; Ali, Nawab; Ali, Essam A.; Bari, Ahmed; Aziz, Muhammad Abdul; Khan, Shahid Niaz
Abstract : Background . Nanotechnology finds broad applications in the field of nanomedicine, an emerging new field used for diagnosis, treatment, prevention of diseases, and improvement of health. Objectives . To synthesize silver nanoparticles (AgNPs) from Withania somnifera and Fagonia indica and to carry out their antimicrobial, insecticidal, and phytotoxic activities, a step toward the new range of nanomedicines. Methods . Silver nanoparticles were synthesized from Withania somnifera and Fagonia indica by chemical reduction method, and further biological activities of these nanoparticles were compared with crude methanolic extract, prepared through cold maceration process, at the concentration of 50 mg/ml. Results . Among all tested bacterial pathogens, crude extract of W. somnifera showed a statistically high significant inhibition zone in millimeter against Pseudomonas aeruginosa (21; p < 0.01 ). AgNPs showed highly significant result against Streptococcus pneumonia (14; p < 0.01 ). In comparison with crude extracts, AgNPs showed statistically significant (p < 0.01 ) results against S. pneumonia (AgNPs, 14; crude, 8.33 mm). Crude extract showed significant inhibition zone against two bacterial strains, P. aeruginosa (crude, 21; AgNPs, 11.67 mm) and Klebsiella pneumoniae (crude, 11.33; AgNPs, 8 mm). Crude extracts of F. indica showed the significant activity against Vibrio cholera (p < 0.01 ; 11.33 mm). Silver nanoparticles of F. indica exhibited the highest significant activity against Aspergillus flavus and Fusarium oxysporum while AgNPs of W. somnifera were active only against A. flavus . Extracts of W. somnifera and F. indica showed increasing phytotoxic activity with increasing concentrations. The highest significant inhibition was obtained for crude extract (46.7) and AgNPs (45.7) of F. indica at 1000  μ g/ml. Insecticidal activity of crude and AgNPs of both plants showed significant inhibition against all tested insects with increasing time intervals, and the highest significant result was obtained at 72 hours with a value of p < 0.01 except T. castaneum . Conclusions . Both crude and AgNPs showed potent activity; however, in comparison, silver nanoparticles showed slightly enhanced activity. Crude and AgNPs of both plants showed good phytotoxic and insecticidal inhibition. Antimicrobial studies of AgNPs on diseases causing pathogens open a door for new antimicrobial agents and could be the answer to antibiotic resistance after further analysis.